The Renovated Thacher Observatory and First Science Results. (1st March 2022) - Swift, Jonathan J.; Andersen, Karina; Arculli, Toby; Browning, Oakley; Ding, Jeffrey; Edwards, Nick; Fanning, Tomás; Geyer, John; Huber, Grace; Jin-Ngo, Dylan; Kelliher, Ben; Kirkpatrick, Colin; et al.
Abstract: Located on the campus of the Thacher School in Southern California, the Thacher Observatory has a legacy of astronomy research and education that dates back to the late 1950s. In 2016, the observatory was fully renovated with upgrades including a new 0.7 m telescope, a research grade camera, and a slit dome with full automation capabilities. The low-elevation site is bordered by the Los Padres National Forest and therefore affords dark to very dark skies allowing for accurate and precise photometric observations. We present a characterization of the site including sky brightness, weather, and seeing, and we demonstrate the on-sky performance of the facility. Our primary research programs are based around our multi-band photometric capabilities and include photometric monitoring of variable sources, a nearby supernova search and followup program, a quick response transient followup effort, and exoplanet and eclipsing binary light curves. Select results from these programs are included in this work which highlight the broad range of science available to an automated observatory with a moderately sized telescope.